CAR-T manufactured from frozen PBMC yield efficient function with prolonged in vitro production - Abraham-Miranda, Julieta; Menges, Meghan; Atkins, Reginald; Mattie, Mike; Kanska, Justyna; Turner, Joel; Hidalgo-Vargas, Melanie J.; Locke, Frederick L. (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-T cells are engineered to identify and eliminate cells expressing a target antigen. Current manufacturing protocols vary between commercial CAR-T cell products warranting an assessment of these methods to determine which approach optimally balances successful manufacturing capacity and product efficacy. One difference between commercial product manufacturing methods is whether T cell engineering begins with fresh (unfrozen) patient cells or cells that have been cryopreserved prior to manufacture. Starting with frozen PBMC material allows for greater manufacturing flexibility, and the possibility of collecting and storing blood from patients prior to multiple lines of therapy. We prospectively analyzed if second generation anti-CD19 CAR-T cells with either CD28 or 4-1BB co-stimulatory domains have different phenotype or function when prepared side-by-side using fresh or cryopreserved PBMCs. We found that cryopreserved PBMC starting material is associated with slower CAR-T cell expansion during manufacture but does not affect phenotype. We also demonstrate that CAR-T cell activation, cytokine production and in vitro anti-tumor cytotoxicity were not different when CAR-T cells were manufactured from fresh or cryopreserved PBMC. As CAR-T cell therapy expands globally, the need for greater flexibility around the timing of manufacture will continue to grow. This study helps support the concept that cryopreservation of PBMCs could be the solution to these issues without compromising the quality of the final CAR-T product.